Expanded expression of pro-neurogenic factor SoxB1 during larval development of gastropod Lymnaea stagnalis suggests preadaptation to prolonged neurogenesis in Mollusca - Kurtova, Anastasia I.; Finoshin, Alexander D.; Aparina, Margarita S.; Gazizova, Guzel R.; Kozlova, Olga S.; Voronova, Svetlana N.; Shagimardanova, Elena I.; Ivashkin, Evgeny G.; Voronezhskaya, Elena E. (Frontiers in Neuroscience, 2024)
Introduction The remarkable diversity observed in the structure and development of the molluscan nervous system raises intriguing questions regarding the molecular mechanisms underlying neurogenesis in Mollusca. The expression of SoxB family transcription factors plays a pivotal role in neuronal development, thereby offering valuable insights into the strategies of neurogenesis. Methods In this study, we conducted gene expression analysis focusing on SoxB-family transcription factors during early neurogenesis in the gastropod Lymnaea stagnalis. We employed a combination of hybridization chain reaction in situ hybridization (HCR-ISH), immunocytochemistry, confocal microscopy, and cell proliferation assays to investigate the spatial and temporal expression patterns of LsSoxB1 and LsSoxB2 from the gastrula stage to hatching, with particular attention to the formation of central ring ganglia. Results Our investigation reveals that LsSoxB1 demonstrates expanded ectodermal expression from the gastrula to the hatching stage, whereas expression of LsSoxB2 in the ectoderm ceases by the veliger stage. LsSoxB1 is expressed in the ectoderm of the head, foot, and visceral complex, as well as in forming ganglia and sensory cells. Conversely, LsSoxB2 is mostly restricted to the subepithelial layer and forming ganglia cells during metamorphosis. Proliferation assays indicate a uniform distribution of dividing cells in the ectoderm across all developmental stages, suggesting the absence of distinct neurogenic zones with increased proliferation in gastropods. Discussion Our findings reveal a spatially and temporally extended pattern of SoxB1 expression in a gastropod representative compared to other lophotrochozoan species. This prolonged and widespread expression of SoxB genes may be interpreted as a form of transcriptional neoteny, representing a preadaptation to prolonged neurogenesis. Consequently, it could contribute to the diversification of nervous systems in gastropods and lead to an increase in the complexity of the central nervous system in Mollusca.